Reference Question Data Mining: A Systematic Approach to Library Outreach - Finnell, Joshua; Fontane, Walt (Reference and user services quarterly, 2010)
This exploratory study investigated the feasibility of using reference questions as an important tool in the construction of study guides, instructional outreach, and collection development at a small, four-year university in Lake Charles, Louisiana. The premise for the study was based on the assumption that the content of the reference question and class from which the question came provide more valuable information than the metadata normally captured within reference classification systems (e.g., directional, research). Reference question subjects received at the reference desk were recorded over six months by the reference staff. The authors then analyzed and classified the data to discover patterns in collection use. The resulting report was then disseminated to the reference, collection development, and instructional outreach departments. The findings reveal that this method of reference data classification and timely reporting provides an excellent reference for planning in these library departments.